014 Diurnal changes in perineuronal nets and parvalbumin neurons in the rat medial prefrontal cortex. (3rd May 2021) - Sorg, Barbara; Harkness, John; Gonzalez, Angela; Bushana, Priyanka; Jorgensen, Emily; Hegarty, Deborah; Nardo, Ariel Di; Prochiantz, Alain; Wisor, Jonathan; Aicher, Sue; Brown, Travis
Abstract: Introduction: Perineuronal nets (PNNs) surrounding fast-spiking, parvalbumin (PV) interneurons provide excitatory:inhibitory balance within cortical circuits. This balance is impaired in several disorders that are also associated with altered diurnal rhythms, yet few studies examined diurnal rhythms of PNNs or PV cells. Methods: We measured the intensity and number of PV cells and PNNs labeled with Wisteria floribunda agglutinin (WFA) and also the oxidative stress marker 8-oxo-deoxyguanosine (8-oxo-dG) in rat prelimbic medial prefrontal cortex (mPFC) at Zeitgeber times (ZT) ZT0, 6, 12, and 18. To examine changes in inhibitory and excitatory inputs to PV cells, we measured GAD 65/67 and vGLUT1 puncta apposed to PV cells with and without PNNs. Whole-cell slice recordings in fast-spiking (PV) cells with PNNs was conducted to determine the ratio of alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor:N-methyl-D-aspartate receptor (AMPA:NMDA) at ZT18 vs. ZT6. Finally, the number of PV cells and PV/PNN cells containing orthodenticle homeobox 2 (OTX2), which maintains PNNs, was also assessed. Results: Relative to ZT0, the intensities of PNN and PV labeling were increased in the dark compared with the light phase. The intensity of 8-oxo-dG was decreased from ZT0 at all times. There were more excitatory puncta on PV cells with PNNs at ZT18 vs. ZT6, but no changes in PV cells without PNNs and no changes in inhibitory puncta. There was an increased AMPA:NMDA ratio at ZT18 vs. ZT6. The number of PV cells and PV/PNN cells containing OTX2 showed a strong trend toward an increase from ZT6 to ZT18, with no differences in non-PV-containing cells. Conclusion: Diurnal fluctuations in PNNs and PV cells alter cortical excitatory:inhibitory balance. Detailed understanding of how these fluctuations are regulated should provide new insights into treatments for diseases impacted by disturbances in sleep and circadian rhythms. Ongoing studies are examining diurnal fluctuations in downstream signaling after PNN removal. Support (if any): Washington State University Alcohol and Drug Abuse Research Program, NIH GM134789 (JHH); NIH DA033404 (BAS), DA040965 (BAS, TEB, SAA); NIH NS078498 (JPW); NIH P30 NS061800 (SAA); and Agence Nationale de la Recherche ANR-18-CE16-0013-01 (AP and AAD).